Effect of double adhesive layer application on micro-tensile dentin bond strength of a universal adhesive - Al-Zain, Afnan O.; Albuqayli, Asrar; Albogami, Abdulaziz; Alkudsi, Abdulghani; Alwabiri, Meshari; Koshak, Abdullah T.; Alsefri, Hattan; Munchow, Eliseu A. (Frontiers in Dental Medicine, 2024)
To evaluate the double adhesive layer application with and without light curing between applications on micro-tensile dentin bond strength (µ-TBS) of a universal adhesive compared to a single layer application. Methods: Intact human molars were divided into three groups (n=15) according to the adhesive application technique using a universal self-etch adhesive (Tetric N-Bond Universal, Ivoclar) as follows: 1) according to the manufacturer's instructions, 2) double-layer application without light curing between layers, and 3) double-layer application with light curing between layers. Samples were immediately tested for TBS, with failure types recorded as adhesive, cohesive, or mixed. Representative samples were observed by scanning electron microscopy. Data were analyzed using multiple-way ANOVA (a=0.05). Results: The double adhesive layer with and without light curing between layers showed similar µ-TBS to that of the control group (p>0.05). Discussion: Double adhesive layer application and light-curing between adhesive layers did not increase the µ-TBS with the universal adhesive agent explored.